2018
DOI: 10.1513/annalsats.201706-426oc
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Significance of Staphylococcus aureus in Patients with Non–Cystic Fibrosis Bronchiectasis

Abstract: Staphylococcus aureus does not appear to be an independent risk factor for severe disease in patients with bronchiectasis enrolled in the Bronchiectasis Research Registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 18 publications
(24 reference statements)
7
19
0
Order By: Relevance
“…The prevalence rate of S. aureus in human pus samples was 38% in the present study. This is in line with a previous study [ 38 ], which isolated S. aureus in 11.3% of patients from sputum specimens. The wide range in the reported prevalence of S. aureus in meat, milk products, and human samples among local and global studies may be attributed to differences in the hygienic measures implemented during food processing and manufacturing in the region of the study.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence rate of S. aureus in human pus samples was 38% in the present study. This is in line with a previous study [ 38 ], which isolated S. aureus in 11.3% of patients from sputum specimens. The wide range in the reported prevalence of S. aureus in meat, milk products, and human samples among local and global studies may be attributed to differences in the hygienic measures implemented during food processing and manufacturing in the region of the study.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of other bacteria may also cause an accelerated clinical deterioration; however, the real impact of such infections has yet to be fully determined 60 . For example, a recent study using a large American database showed that the identification of methicillin-sensitive Staphylococcus aureus does not appear to be an independent risk factor for severe disease in bronchiectasis patients 61 …”
Section: Follow-up and Monitoringmentioning
confidence: 99%
“…Interestingly, S aureus was not associated with severe disease in this cohort. 24 Another study reported 17 cases of S aureus (6 being MRSA) in 233 cases of bronchiectasis, for rates of 7.3% (2.6% MRSA) in Spain. 25 Our reported rate of MRSA and Pseudomonas in bronchiectasis were 4% and 12.1%, respectively, and mortality was 3%.…”
Section: Discussionmentioning
confidence: 99%